UTILIZATION OF THE LABORATORY AND APPLICATION OF SCIENCE PROCESS SKILLS TO INCREASE STUDENT LEARNING OUTCOMES ON THE CONCEPTS OF ELECTROLYTE AND NON-ELECTROLYTE SOLUTIONS CLASS X SMA - Palisoa, Napsin; Lumaela, Miftha Khuljannah (Program Studi Pendidikan Kimia, FKIP, Universitas Pattimura (Chemistry Education Study Program, Faculty of Teacher Training and Educational Sciences, Pattimura University), 2023)
The purpose of this study was to determine the application of science process skills to improving student learning outcomes on the concept of electrolyte and nonelectrolyte solutions for class X SMA Negeri 26 Central Maluku and to determine student responses to learning by using the laboratory. The type of research used is descriptive quantitative research design with one group pretest-posttest design. The research sample was 25 students of class X MIA-1 SMA Negeri 26 Maluku Tengah. Data was collected using test instruments and non-test instruments. The results showed that all students (100%) had reached the KKM. To find out the increase in student learning outcomes, it is calculated using the normalized gain formula (n-gain) where 8 students (32%) are in high qualification and 17 students (68%) are in medium qualification, with an average value of n-gain of 0.7 with a percentage of 70%. For student responses to learning by utilizing laboratories in the form of practicum activities, 17 students (68%) were in the strongly agree qualification, 8 students (32%) were in the agree qualification. Thus the application of science process skills and the use of laboratories has a positive effect on improving learning outcomes.